(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2001)
In this brief didactic revision a few questions concerned to rule-governed behavior are discussed. It is shown that instructed behavior is less sensitive to contingencies than shaped behavior. However, contingency controlled behavior may become rule governed (self-rules). Complex motor behavior as well as those which depend upon subtle response differentiation are more easily taught by instructions but, once established, they may occur without those rules; and they may become completely under contingency control. That means that rules are useful to complement contingencies which are weak, remote, or too complex, as well as in situations of competition between opposing contingencies. However, as those contingencies become stronger (through a more efficient stimulus control or through establishing operations) they overcome rule control.